Architecture, Waste, and the Circular Economy - Ali, Ahmed K. (Enquiry The ARCC Journal for Architectural Research, 2021)
Waste is a modern global crisis. The world is drowning in an unprecedented amount of waste due to an increasing linear economy model that drive societies to consume more every day. It was reported that the average American citizen consume nearly 32 times more that the average Indian citizen. Companies, businesses, and corporates are continuously racing to deplete the planet’s natural resources in an astonishing rate. The design and construction sector alone is responsible for 30-40% of total solid waste worldwide, yet as architects, designers, and planners the waste problem is almost absent from the current discourse, both in practice and academia. Beyond sustainability, and if ideas such as the Dutch “CircularCity” become more appealing to architects, designers, and clients, the architectural education must adopt a transformational shift in the design thinking process to prepare a more responsible future architect. A shift from goal-oriented design to means-oriented design requires a shift in the design education, and the studio pedagogy. A transformation is needed in education, practice, research, and the related professions to address the current and emerging economic challenges more so post crises and pandemics, and through the built environment lens. It is time to define the role of architecture and design in the circular economy paradigm shift.